Association of baseline level of cardiovascular risk burden and its temporal changes with cognitive decline - Ji, Xiaoli; Gao, Hui; Sun, Daoyuan; Zhao, Wensui; Zhuang, Jianlin; Wang, Kan; Ahmadizar, Fariba (Frontiers in Aging Neuroscience, 2022)
Background and Aim: Previous studies on cardiovascular risk burden assessed by the Framingham General Cardiovascular Risk Score (FGCRS) and cognitive trajectories mainly focus on Western populations and most of them have used a single measure of cardiovascular risk. In this study, among middle-aged and older Chinese, we investigated i) the association of baseline FGCRS with subsequent cognitive decline and ii) the association of FGCRS change with concomitant cognitive decline. Methods: In wave 1 to wave 4 (2011 to 2018) of the China Health and Retirement Longitudinal Study, global cognition was assessed by orientation, memory, and executive function. FGCRS was assessed and categorized into tertiles (low, intermediate, and high) at baseline (2011) and 4 years after (2015). Furthermore, external validation was performed to check its generalizability using the English Longitudinal Study of Ageing (ELSA) 2008-2018. Results: 6402 participants with a mean (standard deviation (SD)) age of 57.8 (8.4) years, 49.0% women) with complete baseline data and at least one reassessment of cognitive function were included. A 10% increment in baseline FGCRS was associated with a faster decline in global cognition (-0.010 SD/year, 95%CI -0.013, -0.008). Among 4336 participants (mean (SD) age of 57.8 (8.2) years, 50.0% women) with data on FGCRS changes, compared to individuals with the consistently low FGCRS (reference group), a faster global cognition decline rate was observed in the low to intermediate group (-0.026 SD/year, 95%CI -0.045, -0.007), the low to high group (-0.052 SD/year, 95%CI -0.102, -0.001), the consistently intermediate group (-0.019 SD/year, 95%CI -0.033, -0.005), the intermediate to high group (-0.040 SD/year, 95%CI -0.058, -0.022), the high to intermediate group (-0.024 SD/year, 95%CI -0.047, -0.002), and the consistently high group (-0.047 SD/year, 95%CI -0.060, -0.034). Similar trends were observed for individual cognitive domains. Results from the external validation using the ELSA remained consistent. Conclusions: Higher baseline FGCRS was associated with faster cognitive decline. However, there was no consistent relationship between the direction of changes in FGCRS and cognitive decline.